(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
Based on a single specimen from a new site, located on the Northern Grigna or "Grignone", near the city of Lecco (Lombardy), in the Buchenstein Formation (lower Ladinian), a new taxon belonging to the Perleidiformes is here described. This taxon represents a deep-bodied perleidiform, characterized by a marked hump before the dorsal fin, strongly ornamented scales and a peculiar dentition, made of pencil-like, long and slightly protruding, teeth. Among the other deep-bodied representatives of the order, this new taxon is considered to have more affinities with Felberia, described on material from the late Ladinian of Monte San Giorgio and from the Carnian of the Gorno Formation and Cave del Predil, and "Dipteronotus" ornatus from the late Anisian/early Ladinian of Monte San Giorgio. The exploitation of the new site, started in September 2003, had brought to light until now approximately 900 finds, consisting in the majority of fishes. Despite the state of preservation is not optimal, also probably because of the remarkable heating suffered by the rocks, these finds prove a great diversity (with a fauna similar to that of Monte San Giorgio) and represent the first report of the presence of a fossil vertebrate level in the Buchenstein Formation all over the Southern Calcareous Alps.